Transgender Issues in Indian Society from the Viewpoint of Arundhati Roy’s Novel, The Ministry of Utmost Happiness - Suleman, Danish; Rehman, Faizahani binti Ab (South Asian Journal of Social Sciences and Humanities, 2020)
The transgender community existed from way back in history. There are records for their existence thousands of years ago. But they were always submerged by the society. A chance was never provided for them, which was all that was needed to prove themselves and their existence. The tortures made them escalate downwards in fear of the outer world. The hijras, with their undefined sense of self that forms their understanding of existence, their susceptibility, marginalisation and relocation, existing in the middle of a culture that does not comprehend them and barely tolerates them, are a fitting example of the existential component of precarity. This article attempted to highlight the reason behind the issues faced by transgender community in Indian society. In order to examine these issues this article analysed the character of Anjum, a transgender, in Arundhati Roy’s The Ministry of Utmost Happiness.